Effects of Social Capital on The Development of Dasolin - Ardhiyanti, Lusyta Puri; Soedirham, Oedojo; Devy, Shrimarti Rukmini (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Dasolin (Dana Sosial Ibu Bersalin, or Social Fund for Pregnant Women) is the fund collected from the community voluntarily based on the principle of mutual cooperation in accordance with the collective agreement with the aim of helping finance pregnant womenâs antenatal care, labor and emergency. Social capital is an element capable of fostering the development of Dasolin for success. The purpose of this study was to determine the effects of social capital, which includes trust, reciprocity, member participation, social values and social norms either partially or simultaneously, on the development of Dasolin in Mlaras, Sumobito Sub-district, Jombang Regency. The subject of the present study was 213 pregnant women in Mlaras. Data were collected by using questionnaires. The multiple linear regression was used for statistical analysis. Results showed that social capital, which includes trust, reciprocity, member participation, social values and social norms, had a significant effect on the development of Dasolin in Mlaras, Sumobito Sub-district, Jombang Regency.